NURSING PERFORMANCE IN PATIENTS WITH CHRONIC RENAL FAILURE AND DIABETES MELLITUS - F. Nascimento, Jocinete (Health and Society, 2024)
The goal was to identify the importance of nursing care to the patient with renal impairment and diabetes mellitus. As for the methodology, we opted for a bibliographic review by searching in Latin American and Caribbean Health Sciences (Lilacs), Scientific Eletronic Library Online (Scielo) and Nursing Database (BDEF). and Discussion: It was observed that diabetes is a chronic disease that is characterized by changes in glucose metabolism, whether by poor insulin production-type 1, or by resistance to its action, as it has happened in type 2. That the performance of nursing in the care of patients with diabetes mellitus and chronic renal failure is critical, where the professional employs a systematization of nursing care ensuring the patient a whole and individualized care. It is concluded that the nursing team should act in the promotion of health and/or prevention of diseases such as diabetes and their comorbidities. Also, it was observed in this review that the actions of permanent education and orientation of patients for self-care should be intensely promoted by nurses, among this population who, because they have diabetes mellitus, are pre-discredted the risk factors for development of chronic renal failure.